2019
DOI: 10.3389/fpls.2019.00989
|View full text |Cite
|
Sign up to set email alerts
|

Redox Balance-DDR-miRNA Triangle: Relevance in Genome Stability and Stress Responses in Plants

Abstract: Plants are continuously faced with complex environmental conditions which can affect the oxidative metabolism and photosynthetic efficiency, thus leading to the over-production of reactive oxygen species (ROS). Over a certain threshold, ROS can damage DNA. DNA damage, unless repaired, can affect genome stability, thus interfering with cell survival and severely reducing crop productivity. A complex network of pathways involved in DNA damage response (DDR) needs to be activated in order to maintain genome integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 269 publications
(317 reference statements)
0
23
0
Order By: Relevance
“…Predictive studies were employed as well; Liang et al (2017) reported that MUTL-homolog 1 (MLH1) and MRE11 were putatively targeted by miR5176 and miR5261 in Citrus sinensis whereas the Brachypodium distachyon novel_mir_69 was identified to putatively target the RAD50 mRNA ( Lv et al, 2016 ). Based on recent reviews of literature, an interrelation between DDR, redox systems, and miRNAs, has been proposed ( Cimini et al, 2019 ). Nonetheless, specific hurdles have been pinpointed to explain the poorly represented examples in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Predictive studies were employed as well; Liang et al (2017) reported that MUTL-homolog 1 (MLH1) and MRE11 were putatively targeted by miR5176 and miR5261 in Citrus sinensis whereas the Brachypodium distachyon novel_mir_69 was identified to putatively target the RAD50 mRNA ( Lv et al, 2016 ). Based on recent reviews of literature, an interrelation between DDR, redox systems, and miRNAs, has been proposed ( Cimini et al, 2019 ). Nonetheless, specific hurdles have been pinpointed to explain the poorly represented examples in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Such pl-miRs usually participate in maintaining the basic physiological functions of plants (productivity, resistance to biotic and abiotic stresses, growth and development). For example, developed rice lines overexpressing MIR529a have been shown to have increased resistance to oxidative stress (Chen & Li, 2018; Cimini et al, 2019). The participation of osa-miR159f, osa-miR1871, osa-miR398b, osa-miR408-3p, osa-miR2878-5p, osa-miR528-5p and osa-miR397a in the regulation of a number of physiological processes of rice has been established (Balyan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage of nuclear DNA and mtDNA can be induced by the excessive accumulation of ROS in plant cells, which could also cause epigenetic variations in plants, such as DNA methylation/demethylation (Katsuya-Gaviria et al, 2020;Nagaraja et al, 2021) and histone modifications (Zheng et al, 2021) influencing plant development and growth. DNA damage caused by ROS could trigger the nuclear redox network and affect DNA metabolism through redox-dependent regulatory mechanisms comprising redox buffering and posttranslational modifications, such as the thiol-disulfide switch, glutathionylation, and S-nitrosation (Cimini et al, 2019). Recently, it has been found that ROS can function as catalysts of DNA methylation (Wu and Ni, 2015;Teng et al, 2018).…”
Section: H 2 S and No Affect Mtdna Oxidative Damagementioning
confidence: 99%
“…Exogenous SNP and S-nitrosoglutathione (GSNO), as NO donors, cause the S-nitrosation of Cys49 and Cys53, promoting a conformational change in the secondary structure in proteins of the AtMYB30 transcription factor and inhibiting the DNA binding ability of R2R3-MYB2 from Arabidopsis (Serpa et al, 2007;Tavares et al, 2014). Histone deamination could be repaired through the BER pathway, which is responsible for the repair of damaged single bases resulting from deamination, alkylation, and oxidized bases (Cimini et al, 2019). H 2 S can modify the thiol group of cysteine (-SH) in proteins into a persulfide group (-SSH) through the process of S-sulfhydration, which is considered as the protective mechanism for proteins against oxidative damage (Aroca et al, 2018).…”
Section: H 2 S and No Affect Mtdna Oxidative Damagementioning
confidence: 99%